Analysis Of The Safety Dojo Program To Increase Job Competitiveness Of Titl Graduates In Vocational Education - Ima Ismara, Ketut; Isna, Rauzatul; Purnomo, D (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Research this aim to : (1) know influence variable attitude to power competitive work students in the laboratory competence TITL expertise in SMK (2) know influence habit behavior to power competitive work students in the laboratory competence TITL expertise in SMK (3) knowing influence use safety dojo to power competitive work students in the laboratory competence TITL expertise in SMK and (4) knowing influence attitude , habit behavior and use safety dojo to power competitive work students in the laboratory competence TITL expertise in SMK. Study this use approach study ex post facto with method study mixed (mixed methods) with Triangulation design, using analysis descriptive and analysis regression. Instrument study use observation, documentation, interview, and questionnaire. subject study as many as 17 teachers and 32 participants educate competence TITL expertise. The object of this research is the safety dojo program and the competence of the participants educate competence the TITL expertise needed in the world of work. The results showed that: (1) Attitude variable had a significant positive effect on the work competitiveness of SMK students (β = 0.709, p < 0.05) (2) Behavioral Habits variable partially gave a significant positive influence on the work competitiveness of SMK students (β = 0.342, p < 0.05) (3) The variable of using the Safety Dojo partially gave a significant positive effect on the competitiveness of SMK students (β = 0.196, p < 0.05) and (4) the variables of Attitude, Behavioral Habits, and the Use of the Safety Dojo together gave significant effect on the competitiveness of vocational students (R² = 0.621, F-hit = 27.804, p < 0.05).